1376 Probiotics for Prevention of Necrotizing Enterocolitis in Preterm VLBW Neonates- Systematic Review of Randomised Controlled Trials. (Update 2011). (October 2012) - Deshpande, G; Rao, S; Patole, S; Bulsara, M
Abstract : Background: Systematic reviews indicate significantly lower risk of NEC and mortality, and shorter time to full feeds after probiotic supplementation in preterm (Gestation < 33 weeks) VLBW neonates. 1–3 Few more RCTs have been published since then. Aim: Update our systematic review of probiotic supplementation (Started within first 10 days, duration: 37 days) in preventing 3 stage II NEC in preterm VLBW neonates. Method: Standard Cochrane Neonatal Review Group search strategy was followed. CENTRAL, MEDLINE, EMBASE, CINAHL databases, proceedings (from 2009) of the Pediatric Academic Society meetings and Gastroenterology conferences were searched in September 2011. Results: Total 17 RCTs (N=3147) including rrecently published 5 new RCTs (N= 840) were eligible for inclusion in the meta-analysis. The risk of NEC [RR: 0·39; 95% CI: 0·27, 0·56; p<0.00001] and death (RR: 0·54; 95% CI: 0·41, 0·72) p<0.0001] was significantly lower and the time to full feeds was significantly shorter in the probiotic group (WMD= –2.29 days; 95% CI: –4.25, –0.32; p<0.00001). Risk of sepsis was similar in both groups (RR: 0·92; 95% CI: 0·80, 1·06). Subgroup analysis, according to baseline incidence of NEC (< 6% and ≥6%) also showed significant benefits of probiotics in both scenarios. Conclusions: The results of our updated Meta analysis continue to show the benefits of probiotic supplementation. We have now provided additional evidence of its benefits in units with high as well as low baseline incidence of NEC. References: (1.2): Deshpande et al, Lancet 2007 and Pediatrics 2010 (3): Alfaleh et al 2011.